2015
DOI: 10.2131/fts.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative ions by air purifier have no effects on reproductive function or postnatal growth and development in rats

Abstract: Air purifiers, which release positive and negative ions generated by electric discharge, are widely used in a variety of places. In this study, male and female SD rats [Crl:CD(SD)] were exposed by whole-body inhalation (6 hr/day) to ionized air containing positive and negative ions for at least 10 weeks before mating and throughout the mating, gestation, and lactation periods over two generations, and the effects on the reproductive function of parental animals and development of offspring were assessed. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In the second study, Takasawa et al [ 120 ], investigated whether air ions at ion densities of 1.4, 5.6, and 7.5 million ions/cm 3 can damage the DNA of cells in the lung or blood obtained from rats and mice. A concern for this study, like that of two recent studies from Japan discussed above [ 115 , 116 ], is that the rats were simultaneously exposed to negative and positive air ions at similar levels and this suggests that the resulting concentrations of air ions could be expected to be much lower than reported because of the rapid neutralization of charge by ions of opposite polarity. Damage to DNA is relevant to cancer because damaged DNA, if not repaired by cellular repair mechanisms, can lead to the development of cells with aberrant growth.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the second study, Takasawa et al [ 120 ], investigated whether air ions at ion densities of 1.4, 5.6, and 7.5 million ions/cm 3 can damage the DNA of cells in the lung or blood obtained from rats and mice. A concern for this study, like that of two recent studies from Japan discussed above [ 115 , 116 ], is that the rats were simultaneously exposed to negative and positive air ions at similar levels and this suggests that the resulting concentrations of air ions could be expected to be much lower than reported because of the rapid neutralization of charge by ions of opposite polarity. Damage to DNA is relevant to cancer because damaged DNA, if not repaired by cellular repair mechanisms, can lead to the development of cells with aberrant growth.…”
Section: Resultsmentioning
confidence: 95%
“…Yamamoto et al reported that the maternal body weight, food consumption, uterine weight, as well as the bone development of male and female offspring of rats exposed to high levels of air ions (8500,000 ions/cm 3 ) at both polarities for the first 20 days of pregnancy were no different from those of sham-exposed controls [ 115 ]. The second study from the same laboratory performed a similar experiment but studied the second-generation offspring as well [ 116 ]. However, a concern with both these studies is that the exposure to rats was likely far lower than the study suggests because the rats were exposed simultaneously to positive and negative air ions at equal intensities so rapid neutralization of the ions generated could be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air ions are small particles that exist in nature and are positively or negatively charged molecules or atoms in the air [7]; positively charged ions are positive ions and those negatively charged are negative ions [8]. In addition, air ions containing positive and negative ions have certain abilities such as purification of the atmosphere and deodorization [9].…”
Section: Introductionmentioning
confidence: 99%
“…PCIs are not strong enough to destroy physical barriers or the lung epithelial cells of humans and animals, as they are not capable of damaging DNA or the cytoplasmic protein of bacteria and lung cells [12,13]. Exposure to a 1,000-fold-higher level of PCIs (7,000,000 counts/cm 3 ) than that normally observed in ordinary living conditions showed no toxicological or developmental effects on rats after 10 weeks of treatment [14]. These results indicate that PCIs are harmless to humans and animals under ordinary conditions.…”
Section: Introductionmentioning
confidence: 99%